RECOVERY OF LOGGING RESIDUES THROUGH BALER ON FORWARDER: EXPERIENCE WITH Eucalyptus globulus IN CHILE - Eduardo Acuña; Hector Villalobos; Jorge Cancino; Pablo Mena (Revista Árvore, 2018)
ABSTRACT This study presents results of tests on the recovery of Eucalyptus globulus logging residues. Leftovers were packed with an ENFO-2002 baler on a forwarder, taking advantage of a cut-to-length harvesting system for two conditions of residual biomass, i.e., with and without bark. A continuous field study was carried out, controlling 16.4 scheduled hours in seven days. Delays in the operation stemmed mainly by the visits of the client company and supervision by phone. The baler had an average utilization capacity of 81% for both evaluated conditions and produced an average of 36.2 bales with and 22.2 bales without bark per productive area. An average dry biomass productivity of 5.85 and 5.46 Mg h-1 was reached for similar conditions of residual biomass. Significant differences emerged when the type of harvesting was compared to mean dry weight, between types of harvesting, and mean baling time. Thus, the presence of bark in the logging residues of E. globulus increases the productivity of the baler.